2001
DOI: 10.5194/aab-44-99-2001
|View full text |Cite
|
Sign up to set email alerts
|

Direct and correlated responses to selection for 4-week body weight in two lines of Japanese quails

Abstract: Abstract. Data on 29,411 quails of two selected lines along with a control line were examined over nine generations. Significant genetic gains/generation for 4-week body weight were realized in the two strains (3.70 and 3.10 g). Significant correlated genetic changes were also observed in early body weights (day-old to 3-weeks) as well as in 16-week body weight. Egg number and sexual maturity did not show any significant response while egg weight and egg mass showed desirable genetic gains. Natural selection d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In this study, the rate of inbreeding was 0.33 % in generation 2 up to 1.1 % in generation 4. This result is in agreement with Brah et al (2001) while it is in opposite with Biedermann et al (2009) that reported 4.62 % and 7.12 % at generation 2 and 3, respectively for a population of white park cattle. These high figures of inbreeding are due to the small number of population (11 males and 33 females).…”
Section: Inbreeding and Effective Population Sizesupporting
confidence: 90%
“…In this study, the rate of inbreeding was 0.33 % in generation 2 up to 1.1 % in generation 4. This result is in agreement with Brah et al (2001) while it is in opposite with Biedermann et al (2009) that reported 4.62 % and 7.12 % at generation 2 and 3, respectively for a population of white park cattle. These high figures of inbreeding are due to the small number of population (11 males and 33 females).…”
Section: Inbreeding and Effective Population Sizesupporting
confidence: 90%
“…In general, the heritability values of the four body weight traits are higher for line 2 than for line 1. The estimated heritability of the body weight of the Japanese quail at different ages was reported, for example, by STRONG et al (1978), TOELLE et al (1991), BRAH et al (2001), SAATCI et al (2003, VALI et al (2005) andRESENDE et al (2005). These studies normally used body weights at different ages and often used different methods to estimate the heritability.…”
mentioning
confidence: 99%
“…TOELLE et al (1991) used the simple full-sib analysis for their heritability estimates of the body weight from sire and dam components and reported values between 0.49 and 0.70. BRAH et al (2001) analysed data from 9 generations of two selected quail lines. They found heritability estimates of 4-week body weight between 0.35 and 0.56 using pooled estimates from sire and dam components.…”
mentioning
confidence: 99%
“…Inbreeding depression has previously been reported for these traits (Khaldari et al 2010). Brah et al (2001) with the avoidance of mating between relatives reported Inbreeding levels of 0.32 to 0.43 % per generation that did not appear to be of any significance in affecting the response. Abplanalp (1967) reported that in quail populations three times more inbreeding depression for their entire reproductive cycle relative to domestic fowls can be observed, so in a closed population of quail a loss of 1 % hatchability would be sustained for every increase in the degree of inbreeding (about twice as severe as compared to chicken).…”
Section: Inbreeding and Inbreeding Depressionmentioning
confidence: 80%
“…1999, Baylan et al 2009). Brah et al (2001) reported 9 generations of selection for 4 week body weight had increased the superiority of the selected strains over the control line to 44.2 and 35.9 %. Reddish (2004) reported that 6 generations of selection for pectoralis muscle weight resulted in 2.5 and 27 g improvement in pectoralis muscle weight and body weight in Japanese quail, respectively.…”
Section: Genetic Improvement and Correlated Responsesmentioning
confidence: 99%